Crystallo-co-agglomeration: A novel particle engineering technique - Paradkar, Anant R; Pawar, Atmaram P (Asian Journal of Pharmaceutics (AJP), 2014)
Crystallo-co-agglomeration (CCA) is a novel particle engineering/design technique developed by Kadam et al, to overcome the limitations of spherical crystallization (SC). Basically, it’s single step process used for size enlargement of single, two or more, small dose or large dose drugs, in combination with or without diluent. The process of CCA involves simultaneous crystallization and agglomeration of drug/s with/without excipients/s from good solvent and/or bridging liquid by addition of a non-solvent.Till date CCA has been applied for spherical agglomeration of talc, bromhexine hydrochloride–talc, ibuprofen–talc, ibuprofen–paracetamol, and naproxen–starch. The spherical agglomerates obtained by CCA can be used as intact beads (encapsulated spansules) or directly compressible tablet intermediates having satisfactory micromeritic (flowability), mechanical (friability, crushing), compressional (compressibility, compactibility), and drug release properties. Modified drug release from agglomerates and compacts thereof can be achieved using suitable polymer composition in the process design. Thus, it can be concluded that, CCA is a simple and cost effective process, which can be tailor-made for particle design of all majority of drugs and combinations thereof.